The Emerging Role of the Mammalian Glycocalyx in Functional Membrane Organization and Immune System Regulation - Möckl, Leonhard (Frontiers in Cell and Developmental Biology, 2020)
All cells in the human body are covered by a dense layer of sugars and the proteins and lipids to which they are attached, collectively termed the "glycocalyx". For decades, the organization of the glycocalyx and its interplay with the cellular state have remained enigmatic. This changed in recent years. Latest research has shown that the glycocalyx is an organelle of vital significance, actively involved in and functionally relevant for various cellular processes, that can be directly targeted in therapeutic contexts. This review gives a brief introduction into glycocalyx biology and describes the specific challenges glycocalyx research faces. Then, the traditional view of the role of the glycocalyx is discussed before several recent breakthroughs in glycocalyx research are surveyed. These results exemplify a currently unfolding bigger picture about the role of the glycocalyx as a fundamental cellular agent.